2019
DOI: 10.1093/mnras/stz3069
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the cause of hybrid morphology radio sources (HyMoRS)

Abstract: Hybrid morphology radio sources (HyMoRS) are a rare group of radio galaxies in which differing Fanaroff & Riley morphologies (FR I/II) are observed for each of the two lobes. While they potentially provide insights into the formation of lobe structure, particle acceleration, and the FR dichotomy, previous work on HyMoRS has mainly been limited to low-resolution studies, searches for new candidates, and milliarcsecond-scale VLBI observations of the core region. In this paper, we use new multi-array configuratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 71 publications
(115 reference statements)
3
41
0
Order By: Relevance
“…Recent studies (e.g. Banfield et al, 2015;Kapińska et al, 2017;Harwood et al, 2020) have identified and studied the reasons for the existence of this hybrid class in brighter samples of radio galaxies, and attributed it to environmental effects and asymmetric density environments. Regarding the number of objects identified, Gopal-Krishna & Witta (2001) investigated the literature to find six hybrids, Gawronski et al (2006) report 21 hybrid candidates from the VLA Faint Images of the Radio Sky at Twenty-centimeters (FIRST) survey observed at 4.9 GHz where the sources have flux densities S 1.4GHz > 20 mJy, much brighter than our sample.…”
Section: Comparison To the S 3 -Sex Semi-empirical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies (e.g. Banfield et al, 2015;Kapińska et al, 2017;Harwood et al, 2020) have identified and studied the reasons for the existence of this hybrid class in brighter samples of radio galaxies, and attributed it to environmental effects and asymmetric density environments. Regarding the number of objects identified, Gopal-Krishna & Witta (2001) investigated the literature to find six hybrids, Gawronski et al (2006) report 21 hybrid candidates from the VLA Faint Images of the Radio Sky at Twenty-centimeters (FIRST) survey observed at 4.9 GHz where the sources have flux densities S 1.4GHz > 20 mJy, much brighter than our sample.…”
Section: Comparison To the S 3 -Sex Semi-empirical Simulationmentioning
confidence: 99%
“…More recent studies of radio AGN have revealed a plethora of radio structures which deviate from a straight radio structure, introducing additional classifications, such as head-tail, onesided, wide-/narrow-angle-tail, core-jet, core-lobe, twin-jet, fatdouble, classic-double radio source, compact, jet-less, and even FR0 (e.g. Baldi et al, 2015;Sadler, 2016) and hybrid FRI/FRII (Gopal-Krishna & Witta, 2001;Gawronski et al, 2006;Banfield et al, 2015;Kapińska et al, 2017;Harwood et al, 2020). Furthermore, when the faint radio universe is explored in enhanced sensitivity and resolution, radio sources are discovered that do not follow the FR-type classification.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these structures can exist while the jets appear straight, so jet precession as an origin of X-shaped sources cannot be ruled out on the basis of jets appearing straight. Jets where the precession period is short compared to the source lifetime make complex amorphous morphologies that are perhaps less well matched to typical sources, particularly when the precession angle is also large, although some of the structures produced are reminiscent of restarting or 'double-double' sources (Schoenmakers et al 2000), or hybrid sources (Harwood et al 2020). It may be that jets with short precession periods are rare or short-lived, but further work would be required to explore this.…”
Section: Morphological Comparisons To Real-world Sourcesmentioning
confidence: 99%
“…The 382 objects in our sample were separated based on the code into three categories; FR-I, FR-II and indeterminate. The latter category represents the case where the code cannot clearly determine the morphology, and this is usually the case for more compact objects or objects with non-symmetric lobes where there may be FR-I-like lobes on one side of the jet and FR-II-like lobes on the other, which are likely due to projection effects in many cases (Harwood et al 2020). Due to the ability of LOFAR to observe both compact and extended structures of RLAGN, we expected the code to classify a large number of sources which can be visually identified as either FR-I or FR-II as indeterminate.…”
Section: Observational Propertiesmentioning
confidence: 99%